Membrane Function As Interior Wall To Control The Dynamic Response Of Tanks - Shojaee, Amir; Gheyratmand, Changiz (The Turkish Online Journal of Design Art and Communication, 2016)
Sloshing represents a low-frequency fluctuations of the fluid in the half-full tank which if not controlled effectively, could be as one of the most important factors of destruction and reversal of tanks. Thus, study of the behavior of liquid storage tanks and providing new ways to reduce sloshing and to improve seismic response of tanks, due to the high costs of construction, has considerable importance. In this paper, the ability to control sloshing and demand reduction in external solid walls in two parts using two different methods have been investigated. In the first part, analysis are done in ANSYS finite element software and their accuracy are examined. In the second part, possibility of using membrane wall to improve performance of fluid-structure interaction system in tanks, by studying the behavior and performance of a tank with membrane wall in a manner similar to that mentioned in the first part, is studied. In this case, adjustment of fluid dynamics and structure has been done by tuning the tensile force applied to the membrane and the mass of the membrane, and system response has been compared with rigid tank state to evaluate the effects of applying membrane wall.
Keywords: Liquid Storage Tanks; Fluid-Structure Interaction; Sloshing; Frequency-Domain; Membrane Wall; Sıvı Depolama Tankları; Akışkan-Yapı Etkileşimi; Frekans Domain; Membran Duvar